Construction of an item bank using Rasch analysis - Bahrom, Suhaila; Mat Yaacob, Siti Nubailah; Happas, A'fifah; Saidin, Nurhafizah; Mat Nawi, Mohd Nazim; Shaharom, Nuraslinda (UPSI Press, 2024)
Constructing examination papers has been a lengthy and tedious procedure that is commonly raise by issues with content validity, reliability, and fairness. Therefore, investigating alternative methods such as item banking using Rasch analysis may present a more practical and efficient approach for creating assessments. This study aims to demonstrate how to develop an item bank using Rasch analysis and assess the reliability and validity of the final exam paper for a statistics course that uses item bank as its foundation. In this research, Statistics course which consist of 7 questions are divided into 21 items based on test specification table (TST). The results from Rasch analysis are recorded in an item bank interface created by using excel. The item bank interface facilitates easy access to a large variety of pretested items, allowing for the creation of diverse and balanced exam papers. A well-developed item bank will be a great assistance to exam setters as it makes the process of creating tests easier, faster, and more efficient, which leads to higher-quality examination questions paper.